Influence of hydroxybenzoic acids on the adsorption of Eu(III) onto α, γ-Al2O3 particles in mildly acidic conditions: A macroscopic and spectroscopic study. (November 2016) - Moreau, Pauline; Colette-Maatouk, Sonia; Gareil, Pierre; Reiller, Pascal E.
Abstract: The influence of hydroxybenzoic acids (HAHn ), namely p -hydroxybenzoic acid (4-hydroxybenzoic acid, HPhbH) and protocatechuic acid (3, 4-dihydroxybenzoic acid, HProtoH2 ), on the adsorption of europium(III) onto α, γ-Al2 O3 particles is studied as a function of acid concentration. After measuring the adsorption edge of the Eu(III)/α, γ-Al2 O3 binary system, and using the previously studied binary component system Eu(III)/HAHn —Moreau et al. (2015) Inorg. Chim. Acta 432, 81—, and HAHn /α, γ-Al2 O3 —Moreau et al. (2013) Colloids Surf. A 435, 97—, it is evidenced that HPhbH does not enhance Eu(III) adsorption onto α, γ-Al2 O3 in the Eu(III)/HPhbH/α, γ-Al2 O3 ternary system. Conversely, HProtoH2 enhances Eu(III) adsorption onto α, γ-Al2 O3 in the Eu(III)/HProtoH2 /α, γ-Al2 O3 ternary system. Adsorption of the acids are also found higher in the Eu(III)/acid/α, γ-Al2 O3 ternary systems as compared with the corresponding binary systems assessing synergetic effects. For high HPhbH concentrations, a ternary surface species involving ≡AlOH surface sites, Eu(III), and PhbH – is evidenced by time-resolved luminescence spectroscopy (TRLS). However, in the Eu(III)/HProtoH2 /α, γ-Al2 O3 ternary system, chemical environment of Eu(III) is found to be very close to that in the Eu(III)/HProtoH2 binary system. Ternary surface species could not be evidenced in the Eu(III)/HProtoH2 /α, γ-Al2 O3 ternary system with TRLS because of the very short decay time of Eu(III) in the presence of protocatechuic acid. Highlights: Adsorption in the Eu(III) – hydroxybenzoic acid – alumina system is studied. Adsorption is quantified and luminescence parameters are obtained independently. Synergistic effect of organic acids adsorption are evidenced in the ternary systems. A ternary species is clearly shown for the p -hydrobenzoic acid.